Effect of temperature on the biomass yield, the synthesis of lipids and fatty acid composition of some bacteria (Experimental biology, 2015)
The influence of temperature on the cultivation of biomass yield, total lipid content and fatty acid composition of bacteria Pseudomonas peli, Flavobacterium saliperosum, Bacillus pumilus was studied. It was shown that the temperature reduction during cultivation of the bacteria leads to a decrease in the yield of lipids, but increases the concentration of unsaturated FA at the studied isolates.
Keywords: polyunsaturated fatty acids; microorganisms; culture conditions; total lipids; bacteria